2014
DOI: 10.1093/europace/eut368
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal cooling with ice water does not reduce the incidence of oesophageal lesions complicating catheter ablation of atrial fibrillation: randomized controlled study

Abstract: Oesophageal cooling may alleviate the severity of oesophageal lesions but does not reduce the incidence of this complication under the specific protocol evaluated here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 23 publications
0
43
0
1
Order By: Relevance
“…The protective role of temperature‐triggered instillation of free cold liquid inside the esophagus during CA has been evaluated in different clinical trials with inconsistent results. Kuwahara et al 122 in a randomized controlled study including 100 patients, infused ice water when LET reached 42°C during CA; although the lesions were slightly milder in the cooling group, no significant difference in the incidence of esophageal lesions was found between groups. Despite the risk of aspiration (free liquid inside the esophagus), conscious sedation and periodic esophageal aspiration were performed in all patients, and no bronchoaspiration was reported 122 .…”
Section: Esophageal Protection Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective role of temperature‐triggered instillation of free cold liquid inside the esophagus during CA has been evaluated in different clinical trials with inconsistent results. Kuwahara et al 122 in a randomized controlled study including 100 patients, infused ice water when LET reached 42°C during CA; although the lesions were slightly milder in the cooling group, no significant difference in the incidence of esophageal lesions was found between groups. Despite the risk of aspiration (free liquid inside the esophagus), conscious sedation and periodic esophageal aspiration were performed in all patients, and no bronchoaspiration was reported 122 .…”
Section: Esophageal Protection Strategiesmentioning
confidence: 99%
“…Kuwahara et al 122 in a randomized controlled study including 100 patients, infused ice water when LET reached 42°C during CA; although the lesions were slightly milder in the cooling group, no significant difference in the incidence of esophageal lesions was found between groups. Despite the risk of aspiration (free liquid inside the esophagus), conscious sedation and periodic esophageal aspiration were performed in all patients, and no bronchoaspiration was reported 122 . In a clinical trial including 318 patients undergoing CA using a RF hot balloon‐based isolation, the instillation of a cold mixture containing contrast (Iopamidol) and saline reduced not only the occurrence but the severity of the esophageal injury, especially when a 39°C LET cutoff was used.…”
Section: Esophageal Protection Strategiesmentioning
confidence: 99%
“…al performed a study of 100 patients using very small volumes (5 mL) of ice water as the which was injected prior to RF energy delivery, and subsequently when esophageal temperatures reached 42°C. [18] The severity of the esophageal lesions was qualitatively graded as mild, moderate, or severe, according to their extent and color, with the severe category corresponding to those categorized as grade III or IV by John et al The authors found that this approach reduced the severity of esophageal lesions, but did not reduce their incidence: lesions occurred in 20% of the experimental group, and 22% of the controls, with 3 moderate and 7 mild in the cooled group and 3 severe, 1 moderate, and 7 mild in the control (Fig 2). The percentage of patients free from any ulceration or erosion in each group was found to be 63.6%, 87.5%, and 95.2%, respectively (Fig 3).…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11] Esophageal cooling has also been investigated in multiple studies for the purpose of protecting the esophagus during RF ablation. [12][13][14][15][16][17][18][19][20] Various approaches to cooling have been utilized, including expandable balloon devices, a cooling sac circulating water, and direct instillation of ice-cold water or saline into the esophagus, with investigations utilizing animal models, mathematical models, and human clinical studies. The majority of human clinical studies have utilized direct instillation of ice cold water or saline.…”
Section: Introductionmentioning
confidence: 99%
“…Kuwahara et al reported that AF ablation can result in esophageal injury due to tissue heating at the posterior wall of the left atrium. This heating causes mild ulceration but in rare cases to atrio-esophageal fistulae, a life-threatening complication [66]. In addition, catheter and sheath manipulation can result to tear of the left atrium and mitral valve trauma and avulsion [67].…”
Section: Complications Of Atrial Fibrillation Ablationmentioning
confidence: 99%